Autogenous regulation effect of long-time different load exercise on female endocrine hormone. Issue 4 (October 2019) - Yang, Luhan; Yu, Chao; Lan, Zhaoxi
Endocrine dyscrasia generally is the priority issue bothering the modern woman. To research the regulating effect of the long-term high-intensity aerobic exercise on the secretion of endocrine hormone in women, 80 female postgraduates from a university are selected randomly, and they are divided into control group and exercise group in stochastic average mode; exercise group subjects shall do 8-week aerobic exercise while control group does not do any exercise during the experiment period. Then, locally weighted regression strategy is introduced; partial observed data are utilized to make polynomial weighted fitting to experimental data at the proposed fitting point, and the least square method is utilized for the estimation; finally, effectiveness of the method proposed is verified through a simulation experiment.